Parenting in young mothers: a scoping review - Sumiati Sumiati; Dewi Rokhanawati (International Journal of Health Science and Technology, 2021)
Being a young mother has long-term consequences even during the life of the mother and child in foster care, this hurts both mother and child. The purpose of this review is to look at how childcare in young mothers uses the methodology recommended by Arksey and O'Malley. 11 relevant articles discussed and found key concepts grouped into three main themes namely parenting behavior, parenting stress, and parenting need. Adolescent mothers with higher social support have more knowledge in parenting, parenting attitudes, and self-efficacy in positive parenting, can overcome the temperament of the child, as well as reduce the stress of parenting.